An Empirical Study of Criminalizing Minor Infractions of Tax Laws in Nigeria: The Need for Negotiated Punishments - Oladele, Odetokun Olukayode; Aidonojie, Paul Atagamen; Uzualu, James Emokhai; Ikubanni, Oluwaseye Oluwayomi; Oyedeji, Adefisayo Ifeoluwa (NIU Journal of Humanities; Vol 7 No 2 (2022): NIU Journal of Humanities, Vol. 7 No. 2, June 2022DO - 10.58709/niujhu.v7i2.1481, 2022)
Nigeria’s Constitutions have always recognized the need for tax, and have empowered the legislature to make laws on taxes. However, it has been observed that there are civil and criminal sanctions for certain minor infractions of tax laws, and the usage of specific terms like ‘offences,’ ‘guilty,’ ‘conviction’ and ‘imprisonment’ conveys the idea of criminality. Therefore, the pertinent question is, what are the objectives of the punishments stipulated by the various statutes on tax? To be able to answer this, we made use of online questionnaires sent to 432 respondents residing in the various states of the Federal Republic of Nigeria. The essence of the empirical study is to ascertain the perspective of the general public in criminalizing minor infractions of tax laws and if any of ADR processes are preferably in resolving minor infraction. Descriptive and analytical statistic was use in analyzing the data generated from the questionnaire. The study therefore found that penalties imposed by the tax statutes with regard to minor infractions, are expected to produce common good than inflicting pain. That minor infraction of tax laws should not be criminalized. It was therefore recommended that negotiation (a form of Alternative Dispute Resolution), which is regarded as being more advantageous than the conventional quasi-criminal litigation process, should be adopted in resolving minor infraction of tax laws. Keyword: Tax, Laws, Minor-infractions, Negotiation, Criminal, Punishment